Zimbabwe's Story of Pain and Struggle: Historicity in Bones and Red Hills ofHome - Jenjekwa, Vincent (Scilit, 2022)
This paper critiques Chenjerai Hove’s Bones and Red Hills of Home within the framework of Historical Criticism. It would be argued that Hove’s writings are historical, dwelling on the pain and struggles of Zimbabweans in their fight against colonial domination. The struggle of women against colonialism and male chauvinism is equally pronounced. The two pieces of work carry a sense of cautious optimism: euphoric at the demise of colonialism and cautiously optimistic about the capacity of the new dispensation to deliver the expected change. Already indicators abound in Bones and Red Hills of Home that independence is the beginning of yet new forms of challenges manifested through corrupt political leadership which blatantly betrays the ideals of the struggle, intransigent old structures of government deeply soaked in the nostalgia for colonialism and an economy still tethered to the imperial powerhouse. Though Hove claims to be out rightly historical in his writings, his version of history, in some cases, is rather rudimentary because it has gaping holes in terms of certain historical facts about Zimbabwe. This would be understood against Hove’s own artistic concerns and his standing as a social being.